Investigating the potential of a novel Internet-based cognitive behavioural intervention for Dari and Farsi speaking refugee youth: a feasibility study - Richards, Derek (My University, 2022)
Objective: Over half of the world's forcibly displaced persons are under the age of 25, with many suffering from symptoms of psychological disorders. Many refugees from Afghanistan or Iran speak either Dari or Farsi, which are mutually intelligible dialects of the Persian language. Previous research on adult refugees and immigrants have shown that internet-based cognitive behavioural therapy (ICBT) can be a valuable complement to other forms of treatment. However, there is a lack of knowledge if ICBT is a feasible and acceptable treatment for adolescents and young adults with a refugee background. Method: Fifteen Dari/Farsi-speaking adolescents and young adults between 15 and 26 years of age participated in a feasibility study of a novel individually tailored guided ICBT intervention targeting symptoms of common mental disorders such as anxiety and depression. Self-reported symptoms of anxiety and depression were assessed using the Hopkins Symptom Checklist-25 (HSCL-25) as the primary outcome measure. Four of the treatment participants and three additional non-treatment participants consented to be interviewed regarding the programme's acceptability. The interviews were analysed using Thematic Analysis. Results: The intervention suffered from low adherence, with only 3 participants completing the post-treatment assessment and with participants completing 0.9 modules on average, which meant that the intended quantitative analysis of the pre to post change was not possible. The thematic analysis resulted in two overarching categories, barriers and facilitators, that each contained four themes and related subthemes. Overall, the intervention was deemed culturally relevant and easy to understand. The most salient barriers to participation across interviews concerned interference of symptoms such as concentration difficulties, low energy, and a lack of human contact and support. Conclusion: The current version of the ICBT program demonstrated low feasibility and acceptability in the target population, which mainly seemed to be related to the delivery format. Future studies should investigate if a blended treatment format with regular phone/video calls with a therapist can increase adherence to the intervention.
PUBLISHED
Keywords: Culturally adapted psychotherapy; Internet-based treatment; Adolescents; Feasibility; Acceptability